Design and implementation of prepaid power billing system in smart grid environment - Faizan Rashid; Saim Rasheed; Ahsan Farooq; Majid Ali; Youel Roben; Muhammad Jehanzeb; Abdul Wahab (International Journal of Electrical and Computer Engineering (IJECE), 2022)
This paper presents the real-time monitoring of energy consumption utilizing the global system for mobile communication (GSM) via wireless protocols. The power supply company has the authority to change or alter the tariff rates. The method of payment is prepaid, so there will be options for the customer to request the number of units assigned to the particular meter against the money. The customer can monitor the number of units consumed with the help of GSM. If the units are ten percent of the total units, then the system will give a warning message so that the customer can recharge it before cutting off the supply. A GSM-based wireless module has remote access to the usage of electricity. Simulation is done on Proteus while the hardware is implemented using the microcontroller Arduino Uno.